Anionic surfactant adsorption in detergent sewage with cation ion exchange method - Fernianti, Dewi; ., Wisnu (International Journal of Advanced Chemistry, 2021)
Surfactant is one of chemical substances added in detergent. The surfactant type added in detergent is anionic surfactant, namely Alkyl Benzene Sulfonate (ABS). Alkyl Benzene Sulfonate is a slow-degradable chemical substance due to branched chain in its structure, which causes low oxygen supply from the air due to foam covering the water surface. This condition can cause a dangerous impact for the organisms in the water.This study aimed to adsorb the anionic surfactant contained in detergent sewage using cation exchange resin. Before the adsorption process, cation resin regeneration process was performed following the standard operational procedures of PT. Pertamina RU III, Plaju using 4% H2SO4solution at regeneration time of 45 minutes. Surfactant adsorption process occurred at room temperature with resin mass variables of 50, 100, and 150 g and contact time of 5, 10, 15, 20, and 25 minutes. Furthermore, the surfactant content was analyzed using a spectrophotometer at 652 nm wavelength. The study analysis results showed that the adsorption process of anionic surfactant in the detergent sewage with cation ion exchange method at 50 g resin in 5 – 25 minutes obtained a resin adsorption capacity of 0.72 g, while 150 g resin at 5 – 25 minutes only obtained a resin adsorption capacity of 0.18 g.The best adsorption percentage was achieved from 150 g resin at a contact time of 25 minutes due to adsorbing the anionic surfactant up to 100%. Meanwhile, the closest equation assessment approach was presented fromthe Langmuir adsorption isotherm model by gaining a linear graphic at R2 = 0.9946.